MENINGKATKAN PRESTASI BELAJAR DALAM MENJELASKAN PERKEMBANGAN SISTIM ADMINISTRASI WILAYAH INDONESIA DENGAN MENGGUNAKAN METODE DISKUSI - Maf'ul Maf'ul (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
The aim of the study was to describe the improvement of student achievement against the material of Explaining Regional Administration System Development Indonesia by using discussion method at the sixth graders of the state elementary school Weduni, Deket - Lamongan. The study design was used in the form of action research in three cycles. Each cycle included planning (plan), action (action), observation (observation), and reflection (reflection). The data collected by the test. Based on test results, the application of the method of discussion on the material of Explaining Regional Development Administration System Indonesia has increased significantly. This was evidenced by the results of each test cycle that always increase, i.e 60% of the first cycle, the second cycle 65%, and 74% the third cycle. Thus, the use of discussion method can improve the students’ achievement against the material of Explaining Regional Administration System Development Indonesia.